Physical climate change exposure and firms' adaptation strategy - Li, Xia (Strategic Management Journal, 2025)
Abstract Research Summary This article examines whether and how firms adapt to physical exposures to climate change. I build a novel dataset that compiles information on the adaptation strategies of publicly traded companies around the globe and merge it with climate science data. I find that firms are sensitive to the nature and level of forecasted climate change exposures, and that they adapt more often and more completely to those most salient to their business. Increased physical climate exposure heightens the perceived impact of climate change, leading to a higher degree of adaptation. Furthermore, the positive relationship between firms' climate change exposure and their adaptation is stronger for firms with greater environmental, social, and corporate governance capabilities and those with longer time horizons. Managerial Summary Companies are increasingly exposed to the physical impacts of climate change, yet little is known about how they adapt to these long‐term, systemic, and uncertain changes. This study investigates corporate adaptation strategies in response to climate change. By analyzing climate science data and climate change disclosure information from publicly traded companies worldwide, I find that most firms do not adapt to different physical climate change exposures. They adapt more often and more completely when facing higher forecasted climate exposures. Furthermore, firms' environmental, social, and corporate governance capabilities and their time horizons influence their adaptation to greater climate exposures. These findings suggest that targeted interventions may be necessary to improve corporate adaptation to climate change.